Group 5 ITI Consensus Report: Digital technologies. (17th October 2018) - Wismeijer, Daniel; Joda, Tim; Flügge, Tabea; Fokas, George; Tahmaseb, Ali; Bechelli, Diego; Bohner, Lauren; Bornstein, Michael; Burgoyne, Allan; Caram, Santiago; Carmichael, Robert; Chen, Chun‐Yung; et al.
Abstract: Objectives: Working Group 5 was assigned the task to review the current knowledge in the area of digital technologies. Focused questions on accuracy of linear measurements when using CBCT, digital vs. conventional implant planning, using digital vs. conventional impressions and assessing the accuracy of static computer‐aided implant surgery (s‐CAIS) and patient‐related outcome measurements when using s‐CAIS were addressed. Materials and methods: The literature was systematically searched, and in total, 232 articles were selected and critically reviewed following PRISMA guidelines. Four systematic reviews were produced in the four subject areas and amply discussed in the group. After emendation, they were presented to the plenary where after further modification, they were accepted. Results: Static computer‐aided surgery (s‐CAIS), in terms of pain & discomfort, economics and intraoperative complications, is beneficial compared with conventional implant surgery. When using s‐CAIS in partially edentulous cases, a higher level of accuracy can be achieved when compared to fully edentulous cases. When using an intraoral scanner in edentulous cases, the results are dependent on the protocol that has been followed. The accuracy of measurements on CBCT scans is software dependent. Conclusions: Because the precision intraoral scans and of measurements on CBCT scans and is not high enough to allow for the required accuracy, s‐CAIS should be considered as an additional tool for comprehensive diagnosis, treatment planning, and surgical procedures. Flapless s‐CAIS can lead to implant placement outside of the zone of keratinized mucosa and thus must be executed with utmost care.